(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article analyzes the appropriation of Indigenous cultural expressions in the performing arts and proposes free, prior, and informed consent to decolonize this reality. Through qualitative documentary analysis, academic and legal production was examined. The results offer protocols to apply consent in training and performance production, detailing phases for an ethical and fair dialogue. It is concluded that consent is a political framework that reconfigures power. Despite challenges like asymmetries, its adoption is a pedagogical act that enriches artistic practice with justice, advancing towards decolonization.